The relationship between dysphagia, oral health, masticatory performance and activities of daily living in elderly individuals as assessed by the Eating Assessment Tool - Bayram, Hatice Merve; Ilgaz, Fatma; Serel-Arslan, Selen; Demir, Numan; Rakıcıoğlu, Neslişah (Progress in Nutrition, 2021)
Aim: Poor oral health and tooth loss can lead to a reduction in masticatory performance and activities of daily living (ADL) and affect swallowing. The plan for this study was to determine the relationship between the oral health status, masticatory performance and ADL of elderly individuals with dysphagia and without dysphagia. Methods: The study population consisted of 55 elderly persons with dysphagia (27 male) and 62 elderly persons (24 male) without dysphagia. Dysphagia assessed by Eating Assesssment Tool (EAT-10), the ADL was determined by the Barthel Index (BI) and the oral health status was determined by the Geriatric Oral Health Index (GOHAI). The masticatory performance was evaluated by using a color-changeable chewing gum. Results: Of the dysphagic participants, 69.1% had poor, 27.3% had normal and 3.6% had good masticatory performance (P < .05); 90.9% had severe and 9.1% had moderate oral health problems (P < .001). There was a strong correlation between the GOHAI and EAT-10 scores and a moderate correlation between the GOHAI, masticatory performance and BI scores in the dysphagic individuals  (P < .05). Conclusion: Poor oral health and decreased masticatory performance are directly associated with dysphagia and may lead to a decrease in ADL. When oral health improves or dental treatment is provided, the swallowing function, nutritional status and ADL may improve in elderly individuals. Further studies should evaluate the effect of oral health and masticatory performance on ADL and their efficacy in dysphagia in the long term.